Spatiotemporal variation in acorn production and damage in a Spanish holm oak (Quercus ilex) dehesa - Perez Izquierdo, L; Pulido, F (Forest Systems; Vol 22, No 1 (2013), 2013)
Aim of study. There is a lack of knowledge about spatio-temporal patterns of acorn production in dehesas, especially regarding the influence of different agents causing acorn damage. We examined the spatial and temporal variability on acorn production and damage in four stands within a dehesa farm in 1997, 1998 and 1999. Area of study. The study was carried out in a 1800 ha dehesa farm of Cáceres province, western Spain. Material and Methods. Acorns were sampled by means of seed traps placed in the canopy of six holm oak trees per stand. Acorn collected in it were counted and assessed for damage by Curculio weevils, Cydia moths and the bacterial pathogen Brenneria quercina . Main results. Mean acorn production for the whole study period was 44.60 acorns m -2 , which did not vary significantly either among stands or among years. The variability among individual trees was very high (0-300 acorns m -2 ). The rate of infestation by Curculio was 7.64 ± 10.72 %, by Cydia was 1.76 ± 3.33 %, whereas 10.29 ± 16.12 % of acorns were infested by Brenneria . We found no significant spatial differences, but the rates of acorn loss by insects varied among years. These rates were independent of annual acorn production and there was no correlation among damages by different pests, except between Curculio and Cydia in two crop years. Research highlights. It can be concluded that acorn crops are synchronized at the within-farm level and that the temporal variation in acorn damages can be independent of crop size. Keywords: Acorn production; Brenneria; Curculio; Cydia; dehesa; Quercus ilex; spatio-temporal variation.
Keywords: acorn production; Brenneria; Curculio; Cydia; Dehesa; Quercus ilex; spatio-temporal variation

Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G; Obrador, J J; García, E; Cubera, E; Montero, M J; Pulido, F; Dupraz, C (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources